RESTORAN APUNG SUNGAI KAKAP - Arief, Tazkia Maghfirah Nuraulia; Gultom, Bontor Jumaylinda BR; Khaliesh, Hamdil (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Sungai Kakap Village is a coastal village located at the mouth of the Kapuas River. Sungai Kakap Village offers coastal culinary delights such as seafood and coastal environments often used as photo spots for the enchanting sunrise and sunset. The potential of this coastal area is applied to the design of a floating restaurant. There are four methods used in designing the floating restaurant. Firstly, the design object is the